PEMBAHARUAN NALAR POLITIK - Nur Ihsan Shaleh (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2018)
Political bias continues to resonate in the area of the soul, so its political form touches the boundary at the level of religious values. Will emerging politics continue to ride religion for the sake of the virtual world? Or is religion really going to be a religion that is able to shed light on the world of politics, so it is to be able to give state signs to give benefit to its people. As a Muslim scholar, it should be a religious figure who is able to give a choice to a growing phenomenon. In addition, he must also be able to accept existing differences and minimize extremist characters that do not touch the humanist point, so that religion which is often echoed as a mercy in the universe can be felt. That is, a face capable of protecting all forms of phenomena that continue to echo. Because the religion came down as the main entity in all areas of the problem, both in the family, society and even the nation and state